Perancangan Ontologi Obat Tradisional Bali - Diani, I Dewa Ayu; Ananda, Ngurah; Pramartha, Cokorda; Siaka, Bayu (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
This research aims to develop an ontology that describes the elements involved in the use of traditional Balinese medicine. This ontology was built using the Methontology approach, which consists of a series of systematic stages to design, develop, and evaluate ontologies. In this research, the Balinese traditional medicine ontology includes various main classes such as Traditional Medicines, Medicinal Ingredients, Effects, Drug Types, Latin Names, and Processing, which are connected with relevant relations. Evaluation of the ontology is done using SPARQL to test the consistency and accuracy of the information that can be retrieved from the ontology. The results of this research are expected to contribute to the preservation of Balinese traditional knowledge, especially in documenting and organizing information about Balinese traditional medicine, including the ingredients used, therapeutic effects, drug types, Latin names of ingredients, and processing methods used in making Balinese traditional medicine. The ontology can be used as a basis for the development of a broader knowledge-based information system on Balinese traditional medicine.